2012
DOI: 10.3390/molecules18010128
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antioxidant Compoundsfrom the Stem Bark of Goniothalamus tapisoides Mat Salleh

Abstract: Eleven compounds: goniomicin A (1), goniomicin B (2), goniomicin C (3), goniomicin D (4), tapisoidin (5), goniothalamin (6), 9-deoxygoniopypyrone (7), pterodondiol (8), liriodenine (9), benzamide (10) and cinnamic acid (11), were isolated from the stem bark of Goniothalamus tapisoides. All compounds were identified by spectroscopic analysis and, for known compounds, by comparison with published data. Goniothalamin (6) exhibited mild cytotoxic activity towards a colon cancer cell line (HT-29), with an IC50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…GTN can also be extracted from several other species of Goniothalamus such as Goniothalamus macrophyllus (Alabsi et al, 2012), Goniothalamus tapisoides Mat Salleh (Kim et al, 2012) and Goniothalamus andersonii (Inayat-Hussain et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…GTN can also be extracted from several other species of Goniothalamus such as Goniothalamus macrophyllus (Alabsi et al, 2012), Goniothalamus tapisoides Mat Salleh (Kim et al, 2012) and Goniothalamus andersonii (Inayat-Hussain et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term costs of colorectal cancer, estimated up to be $50,175 per patient in 2009, continue to rise [2]. Colorectal cancer rates have increased rapidly in countries including Taiwan [3], and effective therapeutic solutions are urgently needed [4].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies on Goniothalamus species have led to the identification of a variety of compounds: styryllactones, acetogenins, phenanthrene lactams, naphthoquinones, azaanthraquinones, terpenoids, flavonoids and steroids [3][4][5][6][7][8][9][10]. Several styryllactones have had their cytotoxic activity against human cancer cell lines reported in the literature [11][12][13][14]. This study was initiated by the results of a medicinal plant survey in Phu Dong Ee-Pia Forest, Ubonratana District, Khon Kaen Province, Thailand.…”
Section: Introductionmentioning
confidence: 98%
“…A preliminary biological screen revealed that the crude EtOAc and MeOH extracts from the bark of G. elegants showed cytotoxic activity against the KB oral cavity cancer cell line with % inhibition of 98.09 and 69.12, respectively. In the present work, we report the bioactive constituents, a new 6-epi-goniothalesdiol A (1), nine known styryllactones (2-10) and five known aristolactams (11)(12)(13)(14)(15) isolated from the EtOAc and MeOH extracts of the bark of G. elegants. The isolation and structure elucidation as well as bioactivity evaluation of the isolated compounds are discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation